Who killed the Maya? the vanished civilization - Parthenon Entertainment Ltd.; International Masters Publishers ([New York] : Distributed by International Masters Publishers, 2008)
The Maya were an advanced and powerful people who dominated Central America for over 700 years. Then, around 900 AD, it disappeared within a century. Experts travel deep into the Guatemalan jungle to try and solve the puzzle of what happened to this powerful civilization.
DVD.
Keywords: Indians of Central America; Mayas -- Social life and customs; Mayas; Nonfiction films; Documentary films; DVD-Video discs